Evaluasi Usability dan Perbaikan Desain Antarmuka Pengguna Situs Web Fakultas Pertanian (FP) Universitas Brawijaya - Maria Yulianti; Ismiarta Aknuranda; Niken Hendrakusma Wardani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2017)
Faculty of Agriculture (FP) is one of the faculties at the University of Brawijaya (UB). Students of FP typically utilize a website that addresses http://fp.ub.ac.id/ as a source of information. The results of the initial questionnaire that has been spread to thecollege students of FPstated that they found problems and flaws when using the website. This includes unclear layouts, malfunctioning links, a user interface that is too simple and unattractive, to a low response in accessing the website. IT staff at the FP explains that the website had never been in the related evaluation of usability testing. Usability is an important aspect of the website. with the value of good usability, users can achieve the desired goals with effectiveness, efficiency and satisfaction in a context. Website usability improvements is performed in this study, with the goal of improving usability by making the value of the proposal design. The results of usability testing of website proposaldesign of FP using questionnaires WEBUSE show overall increasing the value of usability. This indicates that the proposal design is better and easier to use than the current design. Website that previously entered into moderate level (grades 0.4-0.6) turns into a good level (grades 0.4-0.8). The increase usability in the category of content, organization and readability as much as 0.07 points, category navigation and links by 0.15 points, user interface design category at 0,11 points and 0.14 points for performance and effectiveness